Morphometric Study of Pituitary Gland with Correlation of Age and Gender using Magnetic Resonance Imaging - Maskey, Sunima; Mansur, Dil Islam; Karki, Subindra; Shrestha, Pragya (Birat Journal of Health Sciences, 2021)
Introduction: The pituitary gland is the master gland of the body. It’s size varies with age and gender. MRI is the safest and effective diagnostic tool for pituitary gland examination.Objectives: This study was aim to determine the anteroposterior, height and transverse dimensions of normal  pituitary gland in different age groups of both sex with MRI.Methodology: It was a descriptive cross-sectional study. It consisted of 567 images of individuals (242 males and 325 females) of various age from 20 to 70 years from the Department of Radio- diagnosis, Dhulikhel Hospital.Results: The mean anteroposterior, height and transverse dimension of pituitary gland is 9.74±1.18 mm, 5.95±1.11 mm and 11.65±2.15 mm respectively in which females have higher value. Independent sample t test showed highly significant differences (p< 0.05) between the mean anteroposterior dimension in males and females. The present study showed the mean value of anteroposterior dimension is maximum at age group 50-59.  The mean value of height, transverse dimension and volume of males and females is maximum at 20-29 age group and minimum at 70-79 age group. One way ANOVA shows that there is significant difference between in height, transverse dimension and volume at different age group (p< 0.05).Conclusion: It was concluded that the height and volume of pituitary gland is maximum at second decade of life then it gradually decreases with age. The mean value of anteroposterior, height and transverse dimension showed greater value of females than males.